Pengaruh Transparansi, Akuntabilitas, Dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa Di Desa Tegalharjo Kecamatan Glenmore Kabupaten Banyuwangi - Dellailatul Nur Afifah; Arik Susbiyani; Ibna Kamelia F. A (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The formulation of the problem in this study is How Transparency, Accountability, and Community Participation regarding Vilage Fund Management in Tegalharjo village, How Transparancy, Accountability, and Community Participation Influence on Village Fund Management. The aim is to find out how Transparency, Accountability, and Community Participation are regarding the Management of Village Fund in Tegalharjo Village, to find out how the Effects of Tranparency, Accountability, and Community Participation in th Management of Village Fund. This type of research is quantitative research. This research was conducted in Tegalharjo Village Glenmore District, Banyuwangi Regency. The variables in this study are Transparancy, Accountability, and Community Participation. The population in this study were all residents of Tegalharjo Village with a total of 4.533 families. The data used primary and secondary data eith data collection techniques using questionnaires. The tests used are valitidy test, rehabilitatio test, classical assumption test, and hypothesis testig. Based on the result of research that has been carried out on all data obtained in Tegalharjo Village, Glenmore District, Banyuwangi Regency, it is concludes that transparency significantly affects the management of village funds, partial accountability significantly affects the management of village funds, partial accountability significantly affects the management of village funds, and community participation significantly affects the management of village fund.